Comparative Study on Production of Antibody in Broilers Vaccinated with Four Lyophilized Newcastle Disease Vaccine - Kamrunnahar, S; Alim, MM; Taslima, AHM; Islam, MA; Paul, NC (Bangladesh Journal of Microbiology, 2011)
A comparative efficacy of four lyophilized Newcastle disease vaccine, namely, Medivac ND-LaSota®, BCRDV®, Izovac B1 Hitchner® and Cevac Vitapest-L® in regard to the production of Himagglutination Inhibition (HI)- antibody was accomplished. For this, a total of 75 chicks were equally divided into five experimental groups such as, A, B, C, D and E. The HI antibody titers of group A vaccinated on 5 and 21 days of age with Medivac NDLaSota ® fluctuated among the Mean ± SD of 89.60 ± 33.05, 102.40 ± 33.05 and 192 ± 67.46 at 15 (10 DPV), 19 (14 DPV) and 31 (26 DPV) days of age respectively. As regards, group B administered with BCRDV® on the same days, the HI titers varied with the Mean ± SD of 83.20 ± 30.91, 102.40 ± 33.04 and 204.80 ± 66.09 at 15 (10 DPV), 19 (14 DPV) and 31 (26 DPV) days of age respectively. When considered the HI antibody titers of group C inoculated with Izovac B1 Hitchner® on days 5 and 21 of age, HI titer exhibited the Mean ± SD of 80.00 ± 43.33, 96.00 ± 33.73 and 192.00 ± 67.46 at 15 (10 DPV), 19 (14 DPV) and 31 (26 DPV) days of age respectively. Elucidation of HI antibody titers of group D birds receiving Cevac Vitapest-L® on same days were recorded to be of Mean ± SD of 96.00 ± 33.73, 115.20 ± 26.98 and 320.00 ± 173.31 at 15 (10 DPV), 19 (14 DPV) and 31 (26 DPV) days of age respectively. In birds of unvaccinated control group E, HI titers were found to be ranged from 32- 64, 16-32, 8-16, 4-8 and 2-4 with Mean ± SD of 48.00 ± 16.87, 24.00 ± 8.43, 11.20 ± 4.13, 5.20 ± 1.93 and 3.40 ± 0.97 on 3, 15, 17, 19 and 31 days of age respectively. Thus, it was found that birds of group A, B, C and D vaccinated with Medivac ND-LaSota®, BCRDV®, Izovac B1 Hitchner® and Cevac Vitapest-L® induced slightly higher level of HI antibody titers than that of BCRDV. Maternally derived antibody (MDA) persisted to a minimal level until the age of chicks of day 17 and later on MDA declined. Keywords: Vaccine; Antibody Titer; Newcastle Disease Virus DOI: http://dx.doi.org/10.3329/bjm.v27i1.9159 BJM 2010; 27(1): 1-5